ProGlycProt V2.0, a repository of experimentally validated glycoproteins and protein glycosyltransferases of prokaryotes. (26th March 2019) - Choudhary, Pravinkumar; Nagar, Rupa; Singh, Vaidhvi; Bhat, Aadil Hussain; Sharma, Yogita; Rao, Alka
Abstract: Knowledge of glycosylation status and glycan-pattern of proteins are of considerable medical, academic and application interest. ProGlycProt V2.0 (www.proglycprot.org ) therefore, is conceived and maintained as an exclusive web-resource providing comprehensive information on experimentally validated glycoproteins and protein glycosyltransferases (GTs) of prokaryotic origin. The second release of ProGlycProt features a major update with a 191% increase in the total number of entries, manually collected and curated from 607 peer-reviewed publications, on the subject. Protein GTs from prokaryotes that catalyze a varied range of glycan linkages are amenable glycoengineering tools. Therefore, the second release presents content that is greatly expanded and reorganized in two sub-databases: ProGPdb and ProGTdb. While ProGPdb provides information about validated glycoproteins (222 entries), ProGTdb catalogs enzymes/proteins that are instrumental in protein glycosylation, directly (122) or as accessory proteins (182). ProGlycProt V2.0 remains highly cross-referenced yet exclusive and complementary in content to other related databases. The second release further features enhanced search capability, a "compare" entries option and an innovative geoanalytical tool (MapView) facilitating location-assisted search-cum filtering of the entries using geo-positioning information of researchers/groups cited in the ProGlycProt V2.0 databases. Thus, ProGlycProt V2.0 continues to serve as a useful one-point web-resource on various evidence-based information on protein glycosylation in prokaryotes.